Regional developments: South Asia [in 2025 GFPR] - Rashid, Shahidur; Dev, S. Mahendra; Joshi, Pramod Kumar; Menon, Purnima (International Food Policy Research Institute, 2025)
Food systems in South Asia have evolved tremendously over the past 50 years, marked by progress in establishing agricultural growth linkages, policymaking and investments in agriculture, and institutional innovations. This chapter examines this evolution, highlighting how policy research has played a critical role in shaping national policies on food security, rural development, and nutrition. Looking ahead to 2050, research on climate change, digitalization, and diets and nutrition will be needed to support South Asia in continuing to build sustainable and resilient food systems that deliver equitable and sustainable outcomes.